High Energy Capacity TiB2/VB2 Composite Metal Boride Air Battery. Issue 3 (1st January 2015) - Stuart, Jessica; Lefler, Matthew; Rhodes, Christopher P.; Licht, Stuart
Abstract : Transition metal borides, such as VB2 and TiB2, are studied as battery anode materials both individually and as a composite anode for an air cathode battery. The combination of VB2 and TiB2 is shown to enhance anodic battery performance. In alkaline media, VB2 and TiB2 anodically discharge to yield respectively 11 and 6 electrons per molecule with VB2 intrinsic gravimetric charge capacity of 4, 060 mAh/g and 2, 314 mAh/g for TiB2, 3 to 5 fold higher than a conventional zinc anode. With an air cathode using external O2, these boride/air batteries discharge at ∼1 V, and exhibit unusually high, primary battery energy capacities. We show that the coulombic efficiency attained by the TiB2 anode in boride/air batteries is not a strong function of the anode capacity per unit area (cm 2 ) of anode, while the efficiency of the VB2 anode decreases with increasing anode capacity. The discharge of VB2 shows a unique singular voltage plateau, indicating that the 11 electrons discharge at a similar potential. Two voltage plateaus are observed during the TiB2 discharge indicating the possibility of a two-step anodic oxidation. The combination of VB2 and TiB2 exhibits evidence of a synergistic increase of the capacity and discharge voltage of boride/air batteries.